Keeping the faith : guidance for Christian women facing abuse - Fortune, Marie M. ([New York, NY] : HarperOne, 1987)
"You are a Christian woman, a woman of faith who has been abused by a member of your family .... You may feel abandoned by your church; you may feel abandoned by God. Now more than ever you need your faith and the support of the community of faith to be with you through this crisis. [This book] is written to ... remind you that God is present to you even now and that there are Christians who do understand your pain, your fear, and your doubt. It is written so that we in the Christian community can keep the faith with you during this time of your life. We will not turn away from you; we will not abandon you. We will walk with you as you seek to end the abuse in your life"--P. [4] of cover.
Includes bibliographical references (p. [101]-103).
Keywords: Abused women -- Pastoral counseling of; Church work with abused women